Heightened Thrombin Generation in Individuals with Resistance to Activated Protein C - Martinelli, Ida; Bottasso, Bianca; Duca, Francesca; Faioni, Elena; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1996)
We chose to evaluate whether or not a state of biochemical hypercoagulability was present in 74 individuals (69 heterozygotes and 5 homozygotes) resistant to activated protein C (APC) due to the Arg506 -> Gin mutation in the factor V gene. To this end, plasma levels of two markers of thrombin formation, prothrombin fragment 1+2 (F1+2) and thrombin-antithrombin complexes (TAT), were measured. High levels of F1+2 and TAT were found in 32% and 23% of APC-resistant individuals vs 4% in controls. The levels of these markers tended to be particularly elevated in three homozygous subjects. A significant positive correlation between F1+2 and TAT was present in APC-resistant individuals. No relationship between marker values and the previous occurrence of thrombotic episodes was found. Therefore, by measuring F1+2 and TAT a state of biochemical hypercoagulability has been identified in about one-third of APC-resistant individuals. This frequency is similar to that previously observed in comparable individuals with inherited deficiencies of protein C and protein S, which are usually associated with a stronger thrombotic tendency than APC-resistant individuals.